Current status of typhoid fever : a review - Chowdhury, MA Jalil; Shumy, Farzana; Anam, Ahmad Mursel; Chowdhury, Mostofa Kamal (Bangladesh Medical Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bmj.v43i2.21394 Bangladesh Med J. 2014 May; 43 (2): 106-111